Proteomic analysis of the response of Rhizopus oryzae ENHE to pentachlorophenol: Understanding the mechanisms for tolerance and degradation of this toxic compound. (August 2020) - Ruiz-Lara, A.; Fierro, F.; Carrasco, U.; Oria, J.A.; Tomasini, A.
Graphical abstract: Highlights: Rhizopus oryzae expressed more proteins when grown with pentachlorophenol than without it. Fungus overexpressed extracellular proteins related to sporulation. Proteins related to energy metabolism help to fungus to tolerate pentachlorophenol. Enzymes involved in pentachlorophenol degradation were identified from proteome of fungus. C2 domain proteins may be help to fungus to tolerate the stress caused by toxic compounds. Abstract: Pentachlorophenol (PCP) is a toxic compound widely distributed in the environment. Rhizopus oryzae ENHE has been shown to possess PCP degradation capacities, peroxidases and phenoloxidases are expected to be involved in the degradation process but no studies have been performed that confirm this hypothesis. We have carried out a proteomic study aiming to understand the mechanisms by which R. oryze tolerates and degrades PCP. After culturing the fungus in media with and without PCP, the secretome and the intracellular proteome were analyzed by shotgun proteomics and 2D-Gel Electrophoresis, respectively. Proteins were identified by LC–MS/MS. In the intracellular proteome, 37 proteins were identified from the spots showing higher intensity or exclusive presence in cultures with PCP. Some redundant identifications of proteins appearing in more than one spot, like proteins belonging to energy metabolism, stress response and cell signaling. Proteins putatively involved in PCP degradation, like peroxidases and a methyltransferase, were also identified. In the secretome, 14 proteins were detected that showed at least 2-fold higher abundance in the broths from cultures with PCP. This work provides new information on the response of R. oryzae to the presence of PCP and allowed the identification of some proteins putatively involved in the degradation of the compound.